SEMINAR ANTIBAKTERI SENYAWA ETANOL BIDARA (Ziziphus mauritiana Lam) TERHADAP PERTUMBUHAN Streptococcu mutans - Jhoti Sumitra; Rangga Lestiawan; Margaretta Olivia (JURNAL PENGMAS KESTRA (JPK), 2021)
Streptococcus mutans, one of the normal microflora in the mouth. However, if it is influenced by predisposing factors, it will become a pathogen. Bidara leaves have antimicrobial activity against Streptococcus mutans, because bidara leaves contain various compounds including alkaloids, flavonoids, tannins, saponins. The purpose of this study was to determine how much inhibition was produced by bidara leaf extract on the growth of Streptococcus mutans bacteria. This research method is an experimental study using the disc diffusion method. The sample of this study was Streptococcus mutans, the dilution of bidara leaf extract consisted of 4 concentrations including: 20%, 40%, 60%, 80%. Amoxicillin was used for positive control. Based on the results of observations showed that the average diameter of the inhibition zone of bidara leaf extract at a concentration of 20% with a diameter of 11,50 mm, at a concentration of 40% and 60% with a diameter of 12,50 mm and 16,06 mm, at a concentration of 80% with a diameter of 17,50 mm. It can be concluded that the higher the concentration of bidara leaf extract, the more the inhibition zone formed will increase. So that bidara leaves are good for use in treating infections caused by Streptococcus mutans bacteria.